(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The science of pedagogy has entered a more important period of development than ever before. Because the future of the independent Republic of Uzbekistan depends on the upbringing of the younger generation. This article deals with current issues in the field of pedagogy in today’s society.